Suppressive potential of bean (Phaseolus vulgaris) flour against five species of stored-product mites (Acari: Acarididae) - Hubert, Jan; Stejskal, Václav; Aspaly, Gamila; Münzbergová, Zuzana (Journal of economic entomology, 2007)
Previous research has demonstrated that legume proteins have insecticidal activity against stored-product pests, but activity against stored-product mites has not been tested. A study was therefore conducted to explore the potential of bean, Phaseolus vulgaris L., flour as novel botanical acaricide against five species of storage and dust mites: Acarus siro L., Aleuroglyphus ovatus (Troupeau), Caloglyphus redickorzevi (Zachvatkin), Lepidoglyphus destructor (Schrank), and Tyrophagus putrescentiae (Schrank). The effect of wheat, Triticum aestivum L., grain enriched with bean flour to eight concentrations (0, 0.01, 0.1, 0.5, 1, 2.5, 5, and 10%) on population growth initiating from the density of 50 mites per 100 g of wheat was recorded for 21 d under laboratory conditions (grain moisture 14.6% moisture content and 25 degree C in darkness). The enrichment of grain with bean flour suppressed the population growth of all tested species: 0.01% concentration reduced population growth of all tested species to >50% in comparison with the control population. The most sensitive species were A. siro and L. destructor, followed by T. putrescentiae and C. redickorzevi. The least sensitive species was A. ovatus. The terminal (i.e., after 21 d) density of mites positively correlated with bean flour concentration. The suppressive effect of bean flour was not linear but rather asymptotic. The results of this study are discussed in the context of the application of bean flour in integrated control of stored-product mites and the elimination of stored-product mite allergens.
Keywords: Population Density; populační růst; populační dynamika; Animals; Population Dynamics; Toxicity Tests; Phaseolus; Triticum; Insect Control; zvířata; Population Growth; pšenice; hustota populace; fazol; testy toxicity; Acaridae; dezinsekce